Pengaruh Asupan Asam Folat dan Kadar Haemoglobin terhadap Perkembangan Neurologis Janin: Systematik Review pada Ibu Hamil - Megawati (STIKES Panca Bhakti Pontianak, 2025)
Background: Fetal neurological development is influenced by maternal nutritional status during pregnancy, particularly folic acid intake and haemoglobin levels. Folic acid plays a role in central nervous system formation, while haemoglobin ensures optimal oxygen supply to the fetal brain. Objective: This study sytematic reviews the effects of folic acid intake and haemoglobin levels on fetal neurological development in pregnant women. Methods: The research design is a systematic review with literature searches in PubMed, Scopus and Science Direct for articles published from 2015 to 2024. The study population is pregnant women, with samples being articles meeting inclusion criteria : observational and experimental studies assessing the relationship between folic acid intake and haemoglobin levels with fetal brain development. Article quality was assessed using the Newcastle-Ottawa Scale and Cochrane Risk of Bias Tool. Results: Review of 10 articles showed that adequate folic acid intake (400-800 mcg/day) and optimal haemoglobin levels (11-13 g/dL) consistently correlate with reduced risk of neural tube defects, delayed cognitive development, and other neurological disorders in the fetus. The combination of folic acid deficiency and anemia doubles the risk of fetal neurological disorders. Conclusion: Monitoring and intervention of folic acid and haemoglobin status in pregnant women are essential to support optimal fetal neurological development. Health workers are advised to strengthen education and monitoring of maternal nutritional status to prevent fetal brain development disorders.